The transformation of Shophouse as an effort to continue the trading tradition in Pasar Baru area, Bandung - Nurtati Soewarno; Mustika Kusumaning Wardhani (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2023)
The development of cities in Indonesia must be connected to the role of the Dutch colonial government. Cities were built from an indigenous village by creating a grid pattern to divide the village into residential blocks with the traditional market as the center. The Chinese, as immigrants, had no choice of work other than being traders. Currently, in Pasar Baru, the first commercial area in Bandung, Chinese-style shophouses are still recognizable, and some have been designated cultural heritage buildings. Unfortunately, some more are no longer intact, split into several units, or transformed into other shophouses. This study aims to show how Chinese society has continued to trade as tradition and how the shophouse as a legacy has adapted. The method used in this research is descriptive qualitative using several case studies. From survey observations, it can be seen that the transformation of shophouses begins with the division of shophouses in a transverse direction so that each unit still has road access to continue the trading tradition. The success of the descendant's continued tradition has made Pasar Baru the most prominent trading center in Bandung and serves other cities around Bandung.